2018
DOI: 10.1155/2018/1797421
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Spinal Epidural and Psoas Abscess in Pregnancy Associated with Intravenous Drug Use

Abstract: Spontaneous spinal epidural abscess (SEA) is a rare infection of the central nervous system. We report a case of a 25-year-old G3 P0020 at 36 weeks of gestational age with history of intravenous drug abuse presenting with acute-onset and severe back pain. Despite antibiotic therapy, pain worsened and she developed lower extremity weakness. Magnetic resonance imaging (MRI) revealed an SEA, and cesarean delivery was performed secondary to increasing weakness, followed by laminectomy (T9-12) and decompression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Three case reports describe a primary psoas abscess in spinal tuberculosis, with bilateral psoas abscesses in two of three cases [ 1 3 ]. Furthermore, two cases of psoas abscesses associated with drug abuse have been described [ 4 , 5 ]. There is only one case report of a psoas abscess in the setting of Crohn's disease in pregnancy [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three case reports describe a primary psoas abscess in spinal tuberculosis, with bilateral psoas abscesses in two of three cases [ 1 3 ]. Furthermore, two cases of psoas abscesses associated with drug abuse have been described [ 4 , 5 ]. There is only one case report of a psoas abscess in the setting of Crohn's disease in pregnancy [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only four cases describe fever, back pain, and pain while moving the ipsilateral leg, defined as the triad of psoas abscess by Hermann Mynter in 1881 [ 3 , 5 , 7 , 8 ]. Our case also shows the difficulty of diagnosis, especially when more common differential diagnoses are in the foreground.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer data suggest that SEA is increasing in prevalence, accounting for around 1 in 1000 hospitalizations, paralleling a rise in immunocompromised states and intravenous drug use [6]. As previously stated, SEA is most commonly the result of regional anesthesia in the peripartum period [4,5]. Additional risk factors include intravenous drug use (IVDU), diabetes mellitus, immunosuppression, and bacteremia [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…SEA is a rare cause of low back pain in pregnancy. There are few reported cases of SEA occurring during pregnancy, majority of which are complications of epidural analgesia during labor and delivery [4,5]. Studies previously had shown SEA to be the cause of 0.2-1.2 in 10,000 of all hospitalizations.…”
Section: Introductionmentioning
confidence: 99%